2023
DOI: 10.1111/jop.13458
|View full text |Cite
|
Sign up to set email alerts
|

Does BRAF V600E mutation affect recurrence rate of ameloblastomas? Systematic review and meta‐analysis

Abstract: ObjectiveThe objective of this systematic review with meta‐analysis was to critically evaluate the available data on the association of the BRAF V600E mutation and recurrence rate of ameloblastomas.Materials and MethodsThis systematic review was registered in Prospero (CRD42020183645) and performed based on the PRISMA statement. A comprehensive search in PubMed, Web of Science, Scopus and Cochrane Library databases was performed in order to answer the question “Does BRAF V600E mutation affect recurrence rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Thus, larger multi‐centre cohorts are needed to establish the correlation between histological type and genotype. In terms of prognosis, a recent systematic review showed no significant differences in recurrence rate between the BRAF p.V600E and BRAF wild‐type AMs 51 …”
Section: Discussionmentioning
confidence: 98%
“…Thus, larger multi‐centre cohorts are needed to establish the correlation between histological type and genotype. In terms of prognosis, a recent systematic review showed no significant differences in recurrence rate between the BRAF p.V600E and BRAF wild‐type AMs 51 …”
Section: Discussionmentioning
confidence: 98%
“…Several recent systematic reviews have conducted meta‐analyses regarding the correlation between BRAF and AM recurrence 29,30 . However, these reviews have not thoroughly evaluated the clinical characteristics and diagnostic efficacy associated with BRAF mutations.…”
Section: Discussionmentioning
confidence: 99%
“…2 Over 65% of the ameloblastomas harbor a missense activating mutation in RAF proto-oncogene, known as BRAF V600E. 1,3,4 This mutation is responsible for the codification of an altered protein that disrupts cell signaling in MAPK pathway and ultimately leads to neoplastic transformation. 2,5,6 Patients with ameloblastoma that displays BRAF mutations are potentially eligible for targeted therapy using MAPK pathway (BRAF, MEK, ERK) inhibitors.…”
Section: Introductionmentioning
confidence: 99%